FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA ONLINE PADA MAHASISWA FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Suci Aulia Fitri; Rr. Srikartikowati Rr. Srikartikowati; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the factors that can affect students' interest in online entrepreneurship. This research uses a quantitative descriptive approach. The population of this research is students of Class 2016, Faculty of Teacher Training and Education, University of Riau. The population of this study were students of the Faculty of Teacher Training and Education, University of Riau, batch 2016. The population was 1,214 people, and the sample was obtained as many as 93 respondents who were taken by simple random sampling technique. Primary data is obtained through a questionnaire distributed via google form. The collected data was then tabulated and analyzed using multiple linear regression with the help of SPSS version 22. The results of multiple linear regression analysis show that the surrounding environment, facilities and infrastructure, facilities have a positive and significant effect on students 'online entrepreneurial interest, while willingness has a negative effect on students' online entrepreneurial interest with the results of the regression equation Y = 6.368 + 0.443X1 + 0.108X2 + 0.122X3 + -0,270 and contributed to student learning outcomes by 28.8%.Key Words: Surrounding Environment, Facilities and Infrastructure,Facilities, Willingness, Interest in Online Entrepreneurship